1998
DOI: 10.1029/97jd01831
|View full text |Cite
|
Sign up to set email alerts
|

Vertical profiling using a complementary kite and tethered balloon platform at Ferryland Downs, Newfoundland, Canada: Observation of a dry, ozone‐rich plume in the free troposphere

Abstract: Abstract. Vertical profiles of ozone mixing ratio, water vapor mixing ratio, and temperature obtained during August 3-13, 1995, at Ferryland Downs, Newfoundland, Canada, as part of the North Atlantic Regional Experiment (NARE) demonstrate the use of high-altitude tethered balloons and kites as measurement platforms. In combination with a novel, fast winching system, previously developed for use with kites, tethered balloons were used for profiling chemical species and meteorological parameters to altitudes as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…A study by Dickerson et al (2007) found that dry convection, with little precipitation, may be especially effective in the vertical transport of aerosols over NE China during spring. Furthermore, as warm air from the polluted continents advects over colder marine air, stable conditions with minimal vertical mixing can be produced (Angevine et al, 1996;Knapp et al, 1998). As a result the pollution layers are isolated from the ocean surface and soluble species, such as aerosols and nitric acid, can be transported hundreds of kilometers downwind at relatively low altitudes (Daum et al, 1996;Neiman et al, 2006;Owen et al, 2006).…”
Section: Y Luan and L Jaeglé: Composite Study Of Aerosol Export Eventsmentioning
confidence: 99%
“…A study by Dickerson et al (2007) found that dry convection, with little precipitation, may be especially effective in the vertical transport of aerosols over NE China during spring. Furthermore, as warm air from the polluted continents advects over colder marine air, stable conditions with minimal vertical mixing can be produced (Angevine et al, 1996;Knapp et al, 1998). As a result the pollution layers are isolated from the ocean surface and soluble species, such as aerosols and nitric acid, can be transported hundreds of kilometers downwind at relatively low altitudes (Daum et al, 1996;Neiman et al, 2006;Owen et al, 2006).…”
Section: Y Luan and L Jaeglé: Composite Study Of Aerosol Export Eventsmentioning
confidence: 99%
“…During these campaigns, the CIRES group obtained excellent height resolution profiles of pressure, temperature, humidity, and ozone as well as other trace gases (see, for example, Baisley et al, 1994;Knapp, et al, 1998). In addition, we also obtained preliminary high-time-resolution temperature and wind velocity fluctuation data to determine atmospheric turbulence properties (Balsley, et al, 1998). These data were typically obtained up to heights extending well above the atmospheric boundary layer.…”
Section: A Brief History Of the Cu Kite Groupmentioning
confidence: 97%
“…Tethered balloon systems have been used to collect tropospheric atmospheric measurements for over 40 years, including profiles of biogenic compounds, chemical species, turbulence, radiation, and meteorological parameters (e.g., Morris et al, 1975;Owens et al, 1982;Greenberg et al, 1998;Knapp et al, 1998;Egerer et al, 2019). Morris et al (1975) developed a portable tethered balloon system that essentially behaved as a tethered radiosonde that was able to be operated by one person at altitudes up to 750 m above ground level (AGL) in wind speeds as high as 10 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…Greenberg et al (1998) further promoted tethered balloon system development by deploying sampling packages used to measured biological volatile organic compounds in the mixed layer in a series of deployments conducted over 11 years. Knapp et al (1998) combined tethered balloon system and kite measurements to study the anticorrelation between ozone and water vapor mixing ratios. Most recently, in Egerer et al (2019 operated sets of 25 instruments to measure turbulent, energy, and radiative fluxes to altitudes of 1.5 km AGL within Arctic clouds.…”
Section: Introductionmentioning
confidence: 99%